ChemInform Abstract: Synthesis, Crystal Structure, Resistivity, Magnetic, and Theoretical Study of ScUS3. Issue 17 (April 2015) - Prakash, Jai; Mesbah, Adel; Ward, Matthew D.; Lebegue, Sebastien; Malliakas, Christos D.; Lee, Minseong; Choi, Eun Sang; Ibers, James A.
Abstract Black needle‐shaped crystals of the title compound are prepared in high yield from stoichiometric amounts of the elements (1173 K, 96 h; slow cooling).